2019
DOI: 10.1007/s12471-019-1254-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiology fellows-in-training are exposed to relatively high levels of radiation in the cath lab compared with staff interventional cardiologists—insights from the RECAP trial

Abstract: Background Interventional cardiologists are inevitably exposed to low-dose radiation, and consequently are at risk for radiation induced diseases like cataract and left-sided brain tumours. Operator behaviour may possibly be the largest influencer on radiation exposure. We hypothesised that awareness regarding radiation exposure grows as skill and the general experience in the catheterization laboratory increase. Objectives In this study we determined the difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…The same results were reported by the study conducted by Vlastra W et al [ 10 ] in 2019 who concluded that fellows-in-training were exposed to a 34% higher relative radiation exposure compared with the staff interventional cardiologists ( p = 0.025). This signifies that these subgroups are at relatively higher risk of radiation hazards, requiring a special attention to both awareness and protection.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The same results were reported by the study conducted by Vlastra W et al [ 10 ] in 2019 who concluded that fellows-in-training were exposed to a 34% higher relative radiation exposure compared with the staff interventional cardiologists ( p = 0.025). This signifies that these subgroups are at relatively higher risk of radiation hazards, requiring a special attention to both awareness and protection.…”
Section: Discussionsupporting
confidence: 84%
“…We also found that among the group of physicians, residents and fellows were the highest subgroups in terms of exposure to radiation because they were exposed to almost the same workload as nurses and technicians when compared to the consultants with P-value < 0.01. The same results were reported by the study conducted by Vlastra W et al [10] in 2019 who concluded that fellows-in-training were exposed to a 34% higher relative radiation exposure compared with the staff interventional cardiologists (p = 0.025). This signifies that these subgroups are at relatively higher risk of radiation hazards, requiring a special attention to both awareness and protection.…”
Section: Discussionsupporting
confidence: 84%
“…The length of the procedure plays a significant role in increasing the staff and patient dose. An experienced doctor might finish the procedure more quickly than a new Cardiology fellows-in-training (12) . The effect of the time of procedure against the dose was evaluated by measuring the dose at the M P explained in the above section.…”
Section: Methodsmentioning
confidence: 99%
“…Rest, physiotherapy and other conservative therapies help in relieving these orthopedic disorders. 16,17 Interventional Cardiologists' working in the cardiac catheterization labs and doing PCI's frequently are exposed to high levels of radiation, which may increase their cancer risk as compared to those cardiologists who are not working in the catheterization labs. 18 In this study, it was observed that the mean duration of working in cardiac catheterization labs was 17.92±4.57 years.…”
Section: Disscussionmentioning
confidence: 99%